(untitled) (Global Journal of Management and Business Research, 2023)
A case study that investigated the rearing of natural resources in territories owned by rural families in the communities of San Isidro and San Pablo, Sierra Occidental de Jalisco, Mexico. The objective was to determine and analyze the strategies generated by the domestic units on the breeding and use of natural resources, taking as a link the birds of the family of the parrots, parrots and macaws, for their popularity as pets, and ease to imitate sounds. We apply a mixed methodology; direct observation, participant and reflective observation, dialogue of knowledge, cultural circles, life stories and a participant rural diagnosis. Community raising of natural resources, a concept that opposes the concept of management, which denotes a colonialist language where natural resources are conceived only from the commercial logic with optimal profits or the intervention of ecosystems by external actors.